Phosphoproteomic analysis of longissimus lumborum of different altitude yaks. (April 2020) - Yang, Yayuan; Han, Ling; Yu, Qunli; Gao, Yongfang; Song, Rende; Zhao, Suonan
Abstract: Yaks in high altitude regions display good adaptability to hypoxic environment. However, the mechanism involved in regulating muscle protein expression in hypoxic environment is not completely clear yet. To explore the mechanisms modulating postmortem alterations, quantitative phosphoproteomic analysis was performed on muscles of yaks raised at two different altitudes. The results indicated that 475 differentially expressed proteins (DEPS) were identified in high-altitude yaks, among which, 439 DEPs were up-regulated and 36 DEPs were down-regulated. Of these, 26 phosphoproteins clustered into energy metabolism and hypoxic adaption were selected after bioinformatics analysis. In addition, some glycolytic enzymes were detected to be differentially phosphorylated. The difference in protein phosphorylation levels between the two groups may be the key factor involved in the regulation of muscle hypoxic adaption. The present results could provide proteomic insights into changes occurring in yak muscles at different altitudes and may be a valuable resource for future investigations.